Seasonal human coronavirus humoral responses in AZD1222 (ChaAdOx1 nCoV-19) COVID-19 vaccinated adults reveal limited cross-immunity - Stanley, Ann Marie; Aksyuk, Anastasia A.; Wilkins, Deidre; Green, Justin A.; Lan, Dongmei; Shoemaker, Kathryn; Tieu, Hong-Van; Sobieszczyk, Magdalena E.; Falsey, Ann R.; Kelly, Elizabeth J. (Frontiers in Immunology, 2024)
Background: Immunity to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is now widespread; however, the degree of cross-immunity between SARS-CoV-2 and endemic, seasonal human coronaviruses (HCoVs) remains unclear. Methods: SARS-CoV-2 and HCoV cross-immunity was evaluated in adult participants enrolled in a US sub-study in the phase III, randomized controlled trial (NCT04516746) of AZD1222 (ChAdOx1 nCoV-19) primary-series vaccination for one-year. Anti-HCoV spike-binding antibodies against HCoV-229E, HCoV-HKU1, HCoV-OC43, and HCoV-NL63 were evaluated in participants following study dosing and, in the AZD1222 group, after a non-study third-dose booster. Timing of SARS-CoV-2 seroconversion (assessed via anti-nucleocapsid antibody levels) and incidence of COVID-19 were evaluated in those who received AZD1222 primary-series by baseline anti-HCoV titers. Results: We evaluated 2,020/21,634 participants in the AZD1222 group and 1,007/10,816 in the placebo group. At the one-year data cutoff (March 11, 2022) mean duration of follow up was 230.9 (SD: 106.36, range: 1-325) and 94.3 (74.12, 1-321) days for participants in the AZD1222 (n = 1940) and placebo (n = 962) groups, respectively. We observed little elevation in anti-HCoV humoral titers post study-dosing or post-boosting, nor evidence of waning over time. The occurrence and timing of SARS-CoV-2 seroconversion and incidence of COVID-19 were not largely impacted by baseline anti-HCoV titers. Conclusion: We found limited evidence for cross-immunity between SARS-CoV-2 and HCoVs following AZD1222 primary series and booster vaccination. Susceptibility to future emergence of novel coronaviruses will likely persist despite a high prevalence of SARS-CoV-2 immunity in global populations. Funding: AstraZeneca; US Government